2014
DOI: 10.2971/jeos.2014.14051
|View full text |Cite
|
Sign up to set email alerts
|

Half-linear cavity multiwavelength Brillouin-erbium fiber laser

Abstract: Multiwavelength half-linear cavity Brillouin erbium fiber laser (BEFL) has been demonstrated. The half-linear cavity BEFL is formed by utilizing only two circulators: one circulator acts as input and output ports and the other circulator is used to form a physical mirror. This design exhibits low peak power difference between the adjacent channels, which is about 0.8 dB. At Brillouin pump (BP) power of 5 dBm and erbium doped fiber (EDF) pump power of 90 mW, up to 19 channels over a wide range of 40 nm (1529 nm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2015
2015
2017
2017

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 19 publications
0
1
0
Order By: Relevance
“…The number of comb lines was limited by the grating bandwidth. A combination of SBS and erbium gain can be used to obtain Brillouin comb generation in random fiber lasers [93][94][95][96]. For example, Mamdoohi et al [94] demonstrated a 28 nm span of Brillouin comb interspaced by 20 GHz in a configuration employing a span of DCF fiber, followed by a 30 cm long highly doped bismuth oxide erbium fiber.…”
Section: Spectral Properties Of Random Fiber Lasers Of Other Typesmentioning
confidence: 99%
“…The number of comb lines was limited by the grating bandwidth. A combination of SBS and erbium gain can be used to obtain Brillouin comb generation in random fiber lasers [93][94][95][96]. For example, Mamdoohi et al [94] demonstrated a 28 nm span of Brillouin comb interspaced by 20 GHz in a configuration employing a span of DCF fiber, followed by a 30 cm long highly doped bismuth oxide erbium fiber.…”
Section: Spectral Properties Of Random Fiber Lasers Of Other Typesmentioning
confidence: 99%